Glass fiber reinforced polyetherimide black particles and preparation method thereof
By adding glass fibers of different shapes and functional fillers to the formula of glass fiber reinforced polyetherimide, the problem of insufficient strength in the prior art is solved, and the strength and toughness of glass fiber reinforced polyetherimide black particles are significantly improved, and it has low cost and good processability.
Patent Information
- Application Number
- CN202510667762.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-06-20
- Estimated Expiration
- 2045-05-23
AI Technical Summary
In the prior art, the strength of glass fiber reinforced polyetherimide black particles is insufficient and cannot meet the growing practical application needs.
By adding glass fibers with round and flat cross-sections to the formulation of glass fiber reinforced polyetherimide, functional fillers with special properties, including scale graphite, aluminum trioxide and tungsten carbide, a composite system is formed by wet ball milling to improve the strength and toughness of the material.
It significantly improves the strength and toughness of glass fiber reinforced polyetherimide black particles, improves the processability and production efficiency of materials, and has the advantages of low cost.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and specifically, to a glass fiber reinforced polyetherimide black pellet and a preparation method thereof. Background Art
[0002] Polyetherimide ( Polyetherimide , abbreviated as PEI) is a special engineering plastic with an ether bond functional group introduced into the polyimide main chain, and has good high temperature resistance, insulation, flame retardancy and chemical stability. The main application fields of polyetherimide include transportation, electronics and electrical appliances, and machinery manufacturing, etc. The conventional formula for preparing glass fiber (GF) reinforced polyetherimide black pellets consists of polyetherimide, glass fiber, and a dye, and is prepared by melt extrusion and pelletizing through a twin-screw extruder.
[0003] The invention patent with the publication number CN101870815A discloses a method of melt extrusion of a thermotropic liquid crystal polymer and polyetherimide to improve the melt flow rate and improve the processing performance of the material, but has the following deficiencies: the addition amount of the thermotropic liquid crystal polymer is 15%, which is too much, losing the advantages of the substrate. The tensile strength of the glass fiber reinforced polyetherimide composite material prepared by adding 40 parts of GF in the PEI matrix is 183 MPa, and the flexural strength is 246 MPa; while the tensile strength of ULTEM™ 2410 (PEI + 40GF) produced by Saudi Basic Industries Corporation (SABIC) is 180 MPa, and the flexural strength is 241 MPa. The strength of the glass fiber reinforced polyetherimide composite material finally prepared by this patent is not significantly improved compared with ULTEM™ 2410.
[0004] The invention patent with the publication number CN102010596B discloses a preparation method of a modified glass fiber reinforced polyetherimide, which improves the compatibility between the modified glass fiber and the polyetherimide matrix, and further improves the mechanical properties of the material, but has the problems of cumbersome modification operation of the glass fiber and serious pollution in the processing process.
[0005] Therefore, it is necessary to prepare a glass fiber reinforced polyetherimide black pellet with high strength to meet the growing actual application requirements. Summary of the Invention
[0006] The present invention provides a glass fiber reinforced polyetherimide black pellet and a preparation method thereof, which solve the problem of insufficient strength of the glass fiber reinforced polyetherimide black pellet in the related art.
[0007] The technical solution of the present invention is as follows: The present invention provides a glass fiber reinforced polyetherimide black pellet, which comprises the following components in parts by weight: 60 - 100 parts of polyetherimide, 1 - 40 parts of glass fiber, 0.5 - 5 parts of functional filler, 0.5 - 1.5 parts of lubricant, and 0.1 - 1 part of color masterbatch; The preparation method of the functional filler comprises the following steps: A1. Wet ball - mill the flake graphite, and then dry it to obtain pretreated flake graphite; A2. Wet ball - mill the pretreated flake graphite, aluminum oxide and tungsten carbide, and then dry it to obtain the functional filler.
[0008] The PEI used in the prior art are all ULTEM™ series products produced by the imported Saudi Basic Industries Corporation (SABIC). The polyetherimide of the present invention is produced by Zhongneng Wanchen Co., Ltd., which has the advantage of low cost.
[0009] As a further technical solution, the glass fiber includes one or both of glass fibers with a flat cross - section and glass fibers with a circular cross - section.
[0010] As a further technical solution, the color masterbatch includes a carrier - free carbon black color masterbatch.
[0011] As a further technical solution, in the carrier - free carbon black color masterbatch, the carbon black content is 55wt% and the high - temperature resistant dispersant content is 45wt%.
[0012] In the present invention, a carrier - free carbon black color masterbatch is added to the formulation of the glass fiber reinforced polyetherimide. The high - temperature resistant dispersant in the color masterbatch has a similar structure to the lubricant. In addition to dispersing carbon black, it can also play a synergistic lubricating role with the lubricant, effectively improving the fluidity of the polyetherimide melt and improving the processability of the polyetherimide material.
[0013] As a further technical solution, the lubricant includes one or more of pentaerythritol tetrastearate, trimethylolpropane fatty acid ester, and polyethylene glycol fatty acid ester.
[0014] The lubricant can be a fluoroplastic or a fatty acid ester, and the fluoroplastic lubricant can be, for example, polytetrafluoroethylene; compared with fluoroplastic lubricants, fatty acid esters have the characteristics of high-efficiency lubricity, environmental protection and biodegradability, can reduce the friction between materials and between materials and the surface of processing equipment, can improve the fluidity of the polyetherimide melt, avoid the adhesion of the melt to the equipment, improve the dispersibility of the glass fiber in the polyetherimide, prevent the glass fiber from being exposed, and can also improve the surface finish of the product; wherein, the fatty acid ester lubricant can be, for example, one or more of butyl stearate, monoglyceride of stearic acid, pentaerythritol tetrastearate, trimethylolpropane fatty acid ester, and polyethylene glycol fatty acid ester, especially when the fatty acid ester lubricant is pentaerythritol tetrastearate, trimethylolpropane fatty acid ester or polyethylene glycol fatty acid ester, in the preparation process of glass fiber reinforced polyetherimide black particles, the lubrication effect is more prominent.
[0015] As a further technical solution, the mass ratio of the glass fiber to the functional filler is 40-60:1.
[0016] As a further technical solution, when the glass fibers are glass fibers with a flat cross section and glass fibers with a circular cross section, the mass ratio of the glass fibers with a flat cross section and the glass fibers with a circular cross section is 4-7:1.
[0017] The prior art adopts the method of adding additives or surface modification of glass fibers to increase compatibility with the matrix, and the performance is improved to a certain extent, but not significantly. The reason is that at a high temperature of nearly 400°C, the additives or surface treatment agents are easy to decompose and become ineffective. Therefore, from the perspective of the appearance of glass fibers, the present invention selects glass fibers with a circular cross section and glass fibers with a flat cross section to be compounded. Since the flow resistance of the flat glass fibers with a cross section similar to that of mica powder when flowing in the polyetherimide resin is significantly smaller than that of the glass fibers with a circular cross section, the melt flow rate is increased, the processability is improved, and the glass fibers are After compounding with glass fibers with circular cross-sections and functional fillers, the toughness of glass fiber reinforced polyetherimide is improved; the glass fibers with circular cross-sections serve as "reinforcers" for flat glass fibers and are oriented along the flow direction of the glass fibers with flat cross-sections. The orderly arranged and evenly dispersed glass fibers with circular cross-sections cooperate with the glass fibers with flat cross-sections to improve the strength and toughness of the glass fiber reinforced polyetherimide black particles; and when the mass ratio of glass fibers with flat cross-sections to glass fibers with circular cross-sections is 4-7:1, the synergistic effect reaches the best.
[0018] As a further technical solution, the mass ratio of the flake graphite, aluminum oxide and tungsten carbide is 3~5:1:1.
[0019] As a further technical solution, in step A1, the dispersion medium for the wet ball milling treatment includes one or more of methanol, ethanol, acetone, and N-methylpyrrolidone. The rotation speed of the wet ball milling treatment is 160 - 280 rpm, and the time is 40 - 50 h; In step A2, the dispersion medium for the wet ball milling treatment includes one or two of polyvinyl alcohol solution and polyacrylamide solution. The rotation speed of the wet ball milling treatment is 500 - 600 rpm, and the time is 15 - 20 h.
[0020] During wet ball milling, in step A1, when pre-treating the flake graphite, when the rotation speed of the ball mill is low, the flaky structure of the flake graphite can be maintained, reducing the deformation and damage of the lamellar layers. In step A2, with the increase of the ball milling speed, the moving speed of the ball milling balls speeds up, the centrifugal force increases, and a higher rotation speed can significantly improve the ball milling efficiency, accelerate the particle refinement speed, and cause local phase transformation and compounding of the powder.
[0021] As a further technical solution, in steps A1 and A2, the ball-to-material ratio during the wet ball milling treatment is independently 2 - 3:1, and the ball milling balls are independently zirconia balls. The zirconia balls are independently composed of zirconia balls with a diameter of 3 mm, zirconia balls with a diameter of 1 mm, and zirconia balls with a diameter of 0.5 mm in a mass ratio of 1:3:1 - 3.
[0022] During ball milling, the zirconia balls are composed of zirconia balls with a diameter of 3 mm, zirconia balls with a diameter of 1 mm, and zirconia balls with a diameter of 0.5 mm in a mass ratio of 1:3:1 - 3. Among them, the ball milling balls with a smaller diameter can refine the powder and improve the uniformity of the powder. The ball milling balls with a larger diameter have a larger mass and kinetic energy, and can generate a stronger impact force during the ball milling process. Using ball milling balls with different diameters for mixed ball milling can improve the ball milling composite effect on the functional filler.
[0023] The present invention also provides a method for preparing glass fiber-reinforced polyetherimide black particles, which is used to prepare the glass fiber-reinforced polyetherimide black particles described above, and includes the following steps: After drying the polyetherimide, it is first mixed with the remaining components of the glass fiber-reinforced polyetherimide black particles except for the glass fiber, and then mixed with the glass fiber and extruded into pellets to obtain the glass fiber-reinforced polyetherimide black particles.
[0024] As a further technical solution, the temperature of the drying treatment is 120 - 150 °C, and the time is 4 - 6 h; The time of the first mixing is 3 - 5 min.
[0025] As a further technical solution, during the extrusion granulation, the temperatures of the twin-screw extruder are set as follows: the temperature of the first zone is 340 °C, the temperature of the second zone is 370 °C, the temperature of the third zone is 380 °C, the temperature of the fourth zone is 380 °C, the temperature of the fifth zone is 390 °C, the temperature of the sixth zone is 390 °C, the temperature of the seventh zone is 390 °C, the temperature of the eighth zone is 380 °C, the temperature of the ninth zone is 380 °C, and the temperature of the die head is 380 °C.
[0026] The temperature setting of the twin-screw extruder is very important in the extrusion granulation process of polymer materials. The temperature setting of the twin-screw extruder in the present invention can fully plasticize the polyetherimide. When mixed with other components, it has excellent material fluidity, is convenient for transportation, and ensures stable extrusion. The surface of the glass fiber reinforced polyetherimide black particles extruded is smooth and there are few defects inside the particles.
[0027] The working principle and beneficial effects of the present invention are as follows: In the present invention, polyetherimide is used as the matrix material to provide basic mechanical properties. Glass fiber can enhance the strength and rigidity of the material, effectively improving the mechanical properties of polyetherimide; when preparing the functional filler, the flake graphite is wet ball milled, impacted and sheared, and after peeling the flake graphite, it is wet ball milled with aluminum oxide and tungsten carbide. The particles rub and collide with each other, enabling aluminum oxide and tungsten carbide to be evenly dispersed on the surface of the pretreated flake graphite, forming a functional filler composite system with special properties. The prepared functional filler and glass fiber jointly build a fiber network in the polyetherimide matrix and form riveting sites, improving the strength of the glass fiber reinforced polyetherimide black particles and also improving the toughness of the glass fiber reinforced polyetherimide black particles. Specific Embodiments
[0028] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the scope of protection of the present invention.
[0029] In the following examples and comparative examples, the model of polyetherimide is VAT002, purchased from Zhongneng Wancheng Co., Ltd.; The model of the glass fiber with a circular cross-section is ECS13-4.5-510H; The model of the glass fiber with a flat cross-section is ECS301HP-3-M3, purchased from Chongqing International Composite Materials Co., Ltd.; The color masterbatch is a carrier-free carbon black masterbatch with a carbon black content of 55 wt% and a high-temperature dispersant content of 45 wt%, purchased from Guangdong Jiucai New Materials Co., Ltd.; The particle size of the flake graphite is 500 μm; The particle size of aluminum oxide is 200 nm; The particle size of tungsten carbide is 200 nm.
[0030] Example 1 The glass fiber reinforced polyetherimide black particles comprise the following components in parts by weight: 60 parts of polyetherimide, 40 parts of glass fiber with a circular cross-section, 1 part of functional filler, 0.5 part of pentaerythritol tetrastearate, and 1 part of color masterbatch; The preparation method of the functional filler comprises the following steps: A1. Place the flake graphite and ethanol in a ball milling tube (the ball-to-material ratio is 2:1, and the ball milling balls are zirconia balls, which are composed of zirconia balls with diameters of 3 mm, 1 mm, and 0.5 mm in a mass ratio of 1:3:1), and carry out wet ball milling treatment at 160 rpm for 50 h, then dry to obtain pretreated flake graphite; the mass-volume ratio of the flake graphite to ethanol is 1 g:5 mL; A2. Place the pretreated flake graphite, aluminum oxide, tungsten carbide, and a 3% polyvinyl alcohol solution in a ball milling tube (the ball-to-material ratio is 2:1, and the ball milling balls are zirconia balls, which are composed of zirconia balls with diameters of 3 mm, 1 mm, and 0.5 mm in a mass ratio of 1:3:1), and carry out wet ball milling treatment at 500 rpm for 20 h, then dry to obtain the functional filler. The mass ratio of the flake graphite, aluminum oxide, and tungsten carbide is 3:1:1; the mass-volume ratio of the flake graphite to the polyvinyl alcohol solution is 1 g:6 mL; The preparation method of the glass fiber reinforced polyetherimide black particles comprises the following steps: Place the polyetherimide in a blast drying oven at 150 °C and dry for 4 h, and mix it with the remaining components of the glass fiber reinforced polyetherimide black particles except for the glass fiber with a circular cross-section for 3 min to obtain a mixture; Place the mixture in the main feeding hopper of a twin-screw extruder, and place the glass fiber with a circular cross-section in the side feeding hopper of the twin-screw extruder, and extrude and pelletize to obtain the glass fiber reinforced polyetherimide black particles; When extruding and pelletizing, the temperature of the twin-screw extruder is set as follows: the temperature of zone 1 is 340 °C, the temperature of zone 2 is 370 °C, the temperature of zone 3 is 380 °C, the temperature of zone 4 is 380 °C, the temperature of zone 5 is 390 °C, the temperature of zone 6 is 390 °C, the temperature of zone 7 is 390 °C, the temperature of zone 8 is 380 °C, the temperature of zone 9 is 380 °C, and the die head temperature is 380 °C.
[0031] Example 2 Glass fiber reinforced polyetherimide black particles, comprising the following components in parts by weight: 60 parts of polyetherimide, 40 parts of glass fiber with a circular cross-section, 1 part of functional filler, 1 part of pentaerythritol tetrastearate, 1 part of color masterbatch; The preparation method of the functional filler comprises the following steps: A1. Place the flake graphite and ethanol in a ball mill tube (ball-to-material ratio of 3:1, the ball mill balls are zirconia balls, and the zirconia balls are composed of zirconia balls with a diameter of 3 mm, zirconia balls with a diameter of 1 mm, and zirconia balls with a diameter of 0.5 mm in a mass ratio of 1:3:3), and carry out wet ball milling treatment at 280 rpm for 40 h, then dry to obtain pretreated flake graphite; the mass-volume ratio of flake graphite to ethanol is 1 g:5 mL; A2. Place the pretreated flake graphite, aluminum oxide, tungsten carbide, and a 3% polyvinyl alcohol solution by mass in a ball mill tube (ball-to-material ratio of 3:1, the ball mill balls are zirconia balls, and the zirconia balls are composed of zirconia balls with a diameter of 3 mm, zirconia balls with a diameter of 1 mm, and zirconia balls with a diameter of 0.5 mm in a mass ratio of 1:3:3), and carry out wet ball milling treatment at 600 rpm for 15 h, then dry to obtain the functional filler. The mass ratio of flake graphite, aluminum oxide, and tungsten carbide is 3:1:1; the mass-volume ratio of flake graphite to the polyvinyl alcohol solution is 1 g:6 mL; The preparation method of the glass fiber reinforced polyetherimide black particles comprises the following steps: Place the polyetherimide in a forced air drying oven at 120 °C and dry for 6 h, then mix it with the remaining components of the glass fiber reinforced polyetherimide black particles except for the glass fiber with a circular cross-section for 4 min to obtain a mixture; Place the mixture in the main feeding hopper of a twin-screw extruder, and place the glass fiber with a circular cross-section in the side feeding port of the twin-screw extruder, and extrude and pelletize to obtain the glass fiber reinforced polyetherimide black particles; When extruding and pelletizing, the temperature of the twin-screw extruder is set as follows: the temperature of zone 1 is 340 °C, the temperature of zone 2 is 370 °C, the temperature of zone 3 is 380 °C, the temperature of zone 4 is 380 °C, the temperature of zone 5 is 390 °C, the temperature of zone 6 is 390 °C, the temperature of zone 7 is 390 °C, the temperature of zone 8 is 380 °C, the temperature of zone 9 is 380 °C, and the die head temperature is 380 °C.
[0032] Example 3 Glass fiber reinforced polyetherimide black particles, comprising the following components in parts by weight: 60 parts of polyetherimide, 40 parts of glass fiber with a circular cross-section, 1 part of functional filler, 1.5 parts of pentaerythritol tetrastearate, 1 part of color masterbatch; The preparation method of the functional filler comprises the following steps: A1. Place the flake graphite and ethanol in a ball milling tube (the ball-to-material ratio is 3:1, and the ball milling balls are zirconia balls, which are composed of zirconia balls with diameters of 3 mm, 1 mm, and 0.5 mm in a mass ratio of 1:3:2). Carry out wet ball milling treatment at 250 rpm for 45 h, and then dry to obtain pretreated flake graphite. The mass-to-volume ratio of flake graphite to ethanol is 1 g:5 mL; A2. Place the pretreated flake graphite, aluminum oxide, tungsten carbide, and a 3% polyvinyl alcohol solution in a ball milling tube (the ball-to-material ratio is 3:1, and the ball milling balls are zirconia balls, which are composed of zirconia balls with diameters of 3 mm, 1 mm, and 0.5 mm in a mass ratio of 1:3:2). Carry out wet ball milling treatment at 500 rpm for 18 h, and then dry to obtain functional fillers. The mass ratio of flake graphite, aluminum oxide, and tungsten carbide is 3:1:1; the mass-to-volume ratio of flake graphite to the polyvinyl alcohol solution is 1 g:6 mL; A method for preparing glass fiber-reinforced polyetherimide black particles, comprising the following steps: Place the polyetherimide in a forced-air drying oven at 130 °C for drying for 5 h, and mix it with the remaining components of the glass fiber-reinforced polyetherimide black particles except for the glass fibers with a circular cross-section for 5 min to obtain a mixture; Place the mixture in the main feeding hopper of a twin-screw extruder, and place the glass fibers with a circular cross-section in the side feeding hopper of the twin-screw extruder, and extrude and pelletize to obtain glass fiber-reinforced polyetherimide black particles; When extruding and pelletizing, the temperature of the twin-screw extruder is set as follows: the temperature of the first zone is 340 °C, the temperature of the second zone is 370 °C, the temperature of the third zone is 380 °C, the temperature of the fourth zone is 380 °C, the temperature of the fifth zone is 390 °C, the temperature of the sixth zone is 390 °C, the temperature of the seventh zone is 390 °C, the temperature of the eighth zone is 380 °C, the temperature of the ninth zone is 380 °C, and the die head temperature is 380 °C.
[0033] Example 4 The difference between this example and Example 3 is only that the glass fibers with a circular cross-section are replaced by glass fibers with a flat cross-section.
[0034] Example 5 The difference between this example and Example 3 is only that eight-ninths of the mass of the glass fibers with a circular cross-section is replaced by an equal amount of glass fibers with a flat cross-section.
[0035] Example 6 The difference between this example and Example 3 is only that three-quarters of the mass of the glass fibers with a circular cross-section is replaced by an equal amount of glass fibers with a flat cross-section.
[0036] Example 7 The difference between this example and Example 3 is only that four-fifths of the mass of glass fibers with a circular cross-section is replaced by an equal amount of glass fibers with a flat cross-section.
[0037] Example 8 The difference between this example and Example 3 is only that seven-eighths of the mass of glass fibers with a circular cross-section is replaced by an equal amount of glass fibers with a flat cross-section.
[0038] Example 9 The difference between this example and Example 3 is only that the glass fiber-reinforced polyetherimide black particles include the following components in parts by weight: 100 parts of polyetherimide, 1 part of glass fibers with a circular cross-section, 5 parts of functional filler, 0.5 part of pentaerythritol tetrastearate, 0.1 part of color masterbatch; the mass ratio of flake graphite, aluminum oxide and tungsten carbide is 5:1:1.
[0039] Example 10 The difference between this example and Example 3 is only that the glass fiber-reinforced polyetherimide black particles include the following components in parts by weight: 80 parts of polyetherimide, 30 parts of glass fibers with a circular cross-section, 0.5 part of functional filler, 1 part of pentaerythritol tetrastearate, 1 part of color masterbatch; the mass ratio of flake graphite, aluminum oxide and tungsten carbide is 4:1:1.
[0040] Comparative Example 1 The difference between this comparative example and Example 1 is only that pentaerythritol tetrastearate and color masterbatch are not added.
[0041] Comparative Example 2 The difference between this comparative example and Example 1 is only that color masterbatch is not added.
[0042] Comparative Example 3 The difference between this comparative example and Example 3 is only that the glass fiber-reinforced polyetherimide black particles include the following components in parts by weight: 60 parts of polyetherimide, 40 parts of glass fibers with a circular cross-section, 0.6 part of flake graphite, 0.2 part of aluminum oxide, 0.2 part of tungsten carbide, 1.5 parts of pentaerythritol tetrastearate, 1 part of color masterbatch.
[0043] Comparative Example 4 The difference between this comparative example and Example 3 is only that the preparation method of the functional filler includes the following steps: Put flake graphite, aluminum oxide, tungsten carbide, and a 3% polyvinyl alcohol solution by mass into a ball mill tube (the ball-to-material ratio is 3:1, and the ball mill balls are zirconia balls, which are composed of zirconia balls with diameters of 3 mm, 1 mm, and 0.5 mm in a mass ratio of 1:3:2). Carry out wet ball milling treatment at 500 rpm for 18 h, and then dry to obtain the functional filler; the mass ratio of flake graphite, aluminum oxide, and tungsten carbide is 3:1:1; the mass-volume ratio of flake graphite and the polyvinyl alcohol solution is 1 g:6 mL.
[0044] Comparative Example 5 The difference between this comparative example and Example 3 is only that aluminum oxide is replaced by tungsten carbide.
[0045] Comparative Example 6 The difference between this comparative example and Example 3 is only that tungsten carbide is replaced by aluminum oxide.
[0046] Experimental Example Perform performance tests on the glass fiber-reinforced polyetherimide black particles prepared in Examples 1-10 and Comparative Examples 1-6 according to the following performance test standards: 1. Density: Test according to Method A of the immersion method in GB / T 1033.1-2008 Plastics - Determination of the density of non-cellular plastics - Part 1: Immersion method, pyknometer method and titration method, with a test temperature of 23 °C, and the result is retained to two decimal places. 2. Tensile strength and elongation at break: Test according to GB / T 1040.2-2022 Plastics - Determination of tensile properties - Part 2: Test conditions for moulded and extruded plastics, with a specimen type of 1A specimen and a test speed of 50 mm / min. 3. Flexural strength: Test according to GB / T 9341-2008 Plastics - Determination of flexural properties, with specimen dimensions of: length 80 mm, width 10 mm, thickness 4 mm; and a test speed of 2 mm / min. 4. Izod impact strength with notched specimen: Test according to GB / T 1043.1-2008 Plastics - Determination of izod impact strength of plastics - Part 1: Non-instrumented impact test, with a notch type of A-notch and a specimen type of 1 specimen. 5. Ash content: Test according to GB / T 9345-2008 Plastics - Determination of ash content, with test method: Method A. 6. Melt flow rate: Test according to ASTM D1238 Standard Test Method for Melt Flow Rates of Thermoplastics by Extrusion Plastometer, with test conditions of 337 °C / 6.6 kgf. Meanwhile, the performance of the glass fiber reinforced polyetherimide black particles prepared in this application was compared with that of Example 4 in the invention patent with the publication number CN101870815A, the glass fiber reinforced polyetherimide product of model ULTEM™ 2410 produced by Sabic, PEI-G40 produced by PRL in the United States, Edgetek™ PI-40GF / 000 BLACK produced by Avient, and OP-PEI 40GF produced by Oxford Polymers Co., Ltd. in the United States. The results are shown in Tables 1 - 2 below. In the tables, "-" represents that the performance was not tested.
[0047] Table 1 Performance test results
[0048] Compared with CN101870815A - Example 4, ULTEM™ 2410, PEI-G40, Edgetek™ PI-40GF / 000 BLACK, and OP-PEI 40GF, the properties such as strength and toughness of the glass fiber reinforced polyetherimide black particles prepared in Examples 1 - 4 of this application have been significantly improved, and it has the advantage of low cost.
[0049] Compared with Comparative Examples 1 - 2, in Example 1, a color masterbatch and a lubricant were added. The color masterbatch contains carbon black. Theoretically, the introduction of carbon black will reduce the melt flow rate of the material and make its processability worse. In the present invention, a carrier-free color masterbatch is added, and its components contain high-temperature resistant dispersants of stearic acid esters, which are similar in structure to the lubricant in the formula. The two produce a synergistic promoting lubrication effect, making up for the disadvantage of poor fluidity of carbon black itself, thereby improving the processability.
[0050] According to the data of Examples 1 - 4, it can be found that as the content of the lubricant increases, the melt flow rate also increases, which can effectively improve the production efficiency and improve the problem of surface floating fibers often appearing in glass fiber reinforced polyetherimide.
[0051] Compared with Example 3, in Example 4, the flat glass fiber has a cross-section similar to mica powder, which is a rectangular structure. This structure will significantly reduce the flow resistance of the flat fiber when flowing in the polyetherimide resin, thereby increasing the melt flow rate and improving the processability.
[0052] Compared with Comparative Examples 3 - 6, the tensile strength and elongation at break of the glass fiber reinforced polyetherimide black particles prepared in Examples 1 - 4 are higher, indicating that when using polyetherimide as the matrix and preparing functional fillers, the flake graphite is first wet ball-milled, and then wet ball-milled with aluminum oxide and tungsten carbide. The prepared functional fillers and glass fibers together improve the strength of the glass fiber reinforced polyetherimide black particles and also improve the toughness.
[0053] Table 2 Performance Test Results
[0054] Compared with Examples 3 - 4, the elongation at break of the glass fiber reinforced polyetherimide black particles prepared in Examples 5 - 8 is higher, indicating that when the glass fiber is a combination of glass fibers with a flat cross-section and glass fibers with a circular cross-section, and then compounded with functional fillers, the toughness of the glass fiber reinforced polyetherimide is improved. Moreover, when the mass ratio of the flat glass fiber to the glass fiber with a circular cross-section in Examples 7 - 8 is 4 - 7:1, the toughness of the glass fiber reinforced polyetherimide reaches an even better level.
[0055] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A glass fiber reinforced polyetherimide black pellet, characterized in that, It comprises the following components in parts by weight: 60 - 100 parts of polyetherimide, 1 - 40 parts of glass fiber, 0.5 - 5 parts of functional filler, 0.5 - 1.5 parts of lubricant, and 0.1 - 1 part of color masterbatch; The preparation method of the functional filler comprises the following steps: A1. Wet ball - mill the flake graphite, and dry it to obtain pretreated flake graphite; A2. Wet ball - mill the pretreated flake graphite, aluminum oxide and tungsten carbide, and dry it to obtain the functional filler.
2. The glass fiber reinforced polyetherimide black pellet according to claim 1, characterized in that, The glass fiber includes one or both of glass fiber with a flat cross - section and glass fiber with a circular cross - section.
3. The glass fiber reinforced polyetherimide black pellet according to claim 1, characterized in that, The color masterbatch includes carrier - free carbon black masterbatch.
4. The glass fiber reinforced polyetherimide black pellet according to claim 1, characterized in that, The lubricant includes one or more of pentaerythritol tetrastearate, trimethylolpropane fatty acid ester, and polyethylene glycol fatty acid ester.
5. The glass fiber reinforced polyetherimide black pellet according to claim 1, characterized in that, The mass ratio of the glass fiber to the functional filler is 40 - 60:
1.
6. The glass fiber reinforced polyetherimide black pellet according to claim 2, characterized in that, When the glass fiber is glass fiber with a flat cross - section and glass fiber with a circular cross - section, the mass ratio of the glass fiber with a flat cross - section to the glass fiber with a circular cross - section is 4 - 7:
1.
7. The glass fiber reinforced polyetherimide black pellet according to claim 1, characterized in that, The mass ratio of the flake graphite, aluminum oxide and tungsten carbide is 3 - 5:1:
1.
8. The glass fiber reinforced polyetherimide black pellet according to claim 1, characterized in that, In step A1, the dispersion medium for the wet ball - milling treatment includes one or more of methanol, ethanol, acetone, and N - methylpyrrolidone. The rotation speed of the wet ball - milling treatment is 160 - 280 rpm, and the time is 40 - 50 h; In step A2, the dispersion medium for the wet ball - milling treatment includes one or both of polyvinyl alcohol solution and polyacrylamide solution. The rotation speed of the wet ball - milling treatment is 500 - 600 rpm, and the time is 15 - 20 h.
9. A method for preparing a glass fiber reinforced polyetherimide black pellet for preparing the glass fiber reinforced polyetherimide black pellet according to any one of claims 1 to 8, characterized in that, It comprises the following steps: After drying the polyetherimide, first mix it with the remaining components of the glass - fiber - reinforced polyetherimide black particles except the glass fiber, and then mix it with the glass fiber and extrude and pelletize to obtain glass - fiber - reinforced polyetherimide black particles.
10. The method for preparing a glass fiber reinforced polyetherimide black pellet according to claim 9, characterized in that, The temperature of the drying treatment is 120 - 150 °C, and the time is 4 - 6 h; The time for the first mixing is 3 - 5 min.
Citation Information
Patent Citations
Glass fibre reinforced polyetherimide and preparation method thereof
CN102010596B
Glass fibre reinforced polyetherimide composite material and preparation method thereof
CN101870815A
Glass fibre reinforced polyetherimide and preparation method thereof
CN102010596A
Method for reducing friction coefficient of polyetherimide by adding bi-component fillers
CN105566905A
Friction and wear resistant articles
CN105849199A